The shape of urban expansion in a middle city in the interior of the pampa bonaerense from an urban-environmental historical perspective (1779-2021) - Giusti, Mariana; Goicoechea, María Eugenia (Revista de Estudios Andaluces, 2021)
The objective of this article is to analyze the forms and trends adopted by the expansion of the built matrix of an intermediate city located in the interior of the Buenos Aires Pampean region (Chascomús, Buenos Aires Province, Argentina). The study covers the period 1779-2021 and focuses on the triad of history, territory and norm. With a methodological design that recovers and systematizes a great empirical base, the following aspects are integrated into the analysis: the effect of historical, economic and social relationships; territorial and environmental characteristics; and the influence of regulations on the forms adopted by urban expansion. The work, in addition to being illustrative of a general context of crisis of the geographic development model based on urban primacy and the questioning of the consolidation of macrocephalic structures, contributes to the knowledge of the difficulties that arise in this type of cities, covering their physical-spatial conformation, its limitations, threats and potentialities.